2012
DOI: 10.2106/jbjs.k.00096
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Results After Gastrocnemius-Soleus Intramuscular Aponeurotic Recession as a Part of Multilevel Surgery in Spastic Diplegic Cerebral Palsy

Abstract: Gastrocnemius-soleus intramuscular aponeurotic recession as a part of multilevel surgery leads to satisfactory correction of mild and moderate equinus deformity in children and adolescents with spastic diplegia without relevant risk for overcorrection and should be preferred over Achilles tendon lengthening to avoid overlengthening. The long-term results in the present study demonstrate that the improvements are long-lasting on average, but individual patients tend to develop recurrence and may need secondary … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
107
2
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 109 publications
(119 citation statements)
references
References 29 publications
9
107
2
1
Order By: Relevance
“…This procedure allows the selective release of the gastrocnemius, while preserving the aponeurotic insertion into the soleus [25]. In the study by Firth et al [14], they observed that only 2.1 mm of gastrocnemius lengthening was achieved after the Baumann procedure with three cuts in the adult formaldehydepreserved cadavers.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This procedure allows the selective release of the gastrocnemius, while preserving the aponeurotic insertion into the soleus [25]. In the study by Firth et al [14], they observed that only 2.1 mm of gastrocnemius lengthening was achieved after the Baumann procedure with three cuts in the adult formaldehydepreserved cadavers.…”
Section: Discussionmentioning
confidence: 99%
“…Generally, both the Baumann procedure and Strayer technique could correct moderate to severe deformity of gastrocnemius equinus, particularly as an ancillary procedure with other reconstructive surgery in the supine position. If contracture of the soleus is additionally present, the recession of the soleus fascia may also be performed through the same incision [25,30]. However, considering the potential merits of the precise segmented lengthening and the intrinsic stability in the Baumann procedure and the anatomic variations in the Strayer procedure, the senior author of our study prefers the Baumann procedure in clinic.…”
Section: Discussionmentioning
confidence: 99%
“…The surgical lengthening should specifically focus only on the contracted muscle, in diplegia typically only the gastrocnemius, with a mid-calf myofascial release. Long-term results suggest that gastrocnemius-soleus intramuscular aponeurotic recession in cases of spastic diplegic CP sufficiently corrects equinus deformity while avoiding overlengthening, which can be detrimental to gait [2]. In hemiplegia, for unknown reasons, the soleus also develops contractures; in this case, a combined slightly more distal myofascial release of the conjoined tendon is preferred.…”
Section: Equinus Deformitymentioning
confidence: 98%
“…A tight gastrocnemius or Achilles tendon, which could be responsible for causing or aggravating heel valgus [4], is addressed with either a gastrocnemius recession or a percutaneous Achilles lengthening, respectively. The Silfverskiold test [29] can be performed intraoperatively and if the equinus improves with knee flexion a gastrocnemius recession is preferred since it is not likely to overlengthen the Achilles, while allowing for a quicker recovery [30]. A medializing calcaneal osteotomy is performed to realign the hindfoot from heel valgus.…”
Section: Stage Iiamentioning
confidence: 99%